2019
DOI: 10.1088/1742-5468/ab16c2
|View full text |Cite
|
Sign up to set email alerts
|

Anderson-like localization transition of random walks with resetting

Abstract: We study several lattice random walk models with stochastic resetting to previously visited sites which exhibit a phase transition between an anomalous diffusive regime and a localization regime where diffusion is suppressed. The localized phase settles above a critical resetting rate, or rate of memory use, and the probability density asymptotically adopts in this regime a non-equilibrium steady state similar to that of the well known problem of diffusion with resetting to the origin. The transition occurs be… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 56 publications
1
20
0
Order By: Relevance
“…While case iii) was originally found in [28] and later in [30], scalings iv) and iv) were found in [31] and, finally, all the asymptotic scalings derived herein were found in [29]. Likewise, transitions between different transport regimes have can possibly emerge as a consequence of spatial [46] or temporal [45] heterogeneities in the resetting process.…”
Section: Spatial Dispersal With Relocations To Visited Placessupporting
confidence: 55%
“…While case iii) was originally found in [28] and later in [30], scalings iv) and iv) were found in [31] and, finally, all the asymptotic scalings derived herein were found in [29]. Likewise, transitions between different transport regimes have can possibly emerge as a consequence of spatial [46] or temporal [45] heterogeneities in the resetting process.…”
Section: Spatial Dispersal With Relocations To Visited Placessupporting
confidence: 55%
“…In contrast, for r > r c (γ), the walker gets localised, i.e. p(n, t) becomes stationary at late times and the stationary distribution has an exponential tail with a characteristic localization length scale ξ(r) that diverges as one approaches the critical line as ξ (r − r c ) −ν where ν takes the same value as in the self-consistent theory of Anderson localization of waves in random media [146,147]. The critical value r c (γ) was shown to be related to the probability P no−return of no-return to the origin for the free random walker, i.e, without resetting, via the simple relation…”
Section: Localization-delocalization Transition Induced By Preferentimentioning
confidence: 99%
“…It was shown that the RWs perform slow sub-diffusion due to the dynamics of memory-driven resetting [61,62]. The model above was further studied in the presence of a single defect site where the RW stays with a finite probability [63,64]. Another discrete time RW on a lattice was considered in [65] where resetting with a probability relocated the walker to the previous maximum.…”
Section: Introductionmentioning
confidence: 99%